Faktor Yang Berhubungan Dengan Ketidaklancaran Proses Persalinan Normal - Petan, Veronika Uba; Wahyuni, Maria M. Dwi; Sir, Amelya B. (Timorese Journal of Public Health, 2019)
The result of not fluent parturition will cause infection, bleeding, fatigue, anxiety, premature rupture of membranes, fetal injury and asphyxia in infants that can increase maternal and infant mortality. Health Office Data in NTT 2013 showed that the number of maternal deaths in the district Lembata 3 cases out of 3.075 labors. The infant mortality rate as much 67 cases and as much 32 cases of neonatal mortality.The infant mortality rate in the district Lembata is still quite high enough that ranks 6 of 21 districts in NTT Province. The purpose of this study was to analyze factors associated with disfluencies parturition in a public hospital district Lewoleba-Lembata 2015. This research method is an analytical observation with a cross-sectional survey design by interviewing mothers in maternity hospitals in an obstetrics room of 60 people. Data analysis using the Chi-Square test to determine factors associated with not fluent, then proceed with the contingency coefficient test to determine the relationship variable, if the value of p <0.05. The results showed, there is a significant relationship between maternal age (p=0.002), maternal nutritional status (p=0.034), family support (p=0.047), compliance with antenatal care (p=0.007) with not fluent parturition. Recommended for health care workers to perform program planning relating to the extension to women of childbearing age to prevent risk factors that can cause not fluent parturition.